Characteristics of children with unilateral hearing loss. (2nd November 2017) - Fitzpatrick, Elizabeth M.; Al-Essa, Rakan S.; Whittingham, JoAnne; Fitzpatrick, Jessica
Abstract: Objective : The purpose of this study was to describe the clinical characteristics of children with unilateral hearing loss (UHL), examine deterioration in hearing, and explore amplification decisions. Design : Population-based data were collected prospectively from time of diagnosis. Serial audiograms and amplification details were retrospectively extracted from clinical charts to document the trajectory and management of hearing loss. Sample : The study included all children identified with UHL in one region of Canada over a 13-year period (2003–2015) after implementation of universal newborn hearing screening. Results : Of 537 children with permanent hearing loss, 20.1% (108) presented with UHL at diagnosis. They were identified at a median age of 13.9 months (IQR: 2.8, 49.0). Children with congenital loss were identified at 2.8 months (IQR: 2.0, 3.6) and made up 47.2% ( n = 51), reflecting that a substantial portion had late-onset, acquired or late-identified loss. A total of 42.4% ( n = 39) showed deterioration in hearing, including 16 (17.4%) who developed bilateral loss. By study end, 73.1% (79/108) of children had received amplification recommendations. Conclusions : Up to 20% of children with permanent HL are first diagnosed with UHL. About 40% are at risk for deterioration in hearing either in the impaired ear and/or in the normal hearing ear.